Pontin is localized in nucleolar fibrillar centers - Cvacková, Zuzana; Albring, Kai F; Koberna, Karel; Ligasová, Anna; Huber, Otmar; Raska, Ivan; Stanek, David (Chromosoma, 2008)
Pontin is a multifunctional protein having roles in various cellular processes including regulation of gene expression. Here, we addressed Pontin intracellular localization using two different monoclonal antibodies directed against different Pontin epitopes. For the first time, Pontin was directly visualized in nucleoli where it co-localizes with Upstream Binding Factor and RNA polymerase I. Nucleolar localization of Pontin was confirmed by its detection in nucleolar extracts and by electron microscopy, which revealed Pontin accumulation specifically in the nucleolar fibrillar centers. Pontin localization in the nucleolus was dynamic and Pontin accumulated in large nucleolar dots mainly during S-phase. Pontin concentration in the large nucleolar dots correlated with reduced transcriptional activity of nucleoli. In addition, Pontin was found to associate with RNA polymerase I and to interact in a complex with c-Myc with rDNA sequences indicating that Pontin is involved in the c-Myc-dependent regulation of rRNA synthesis.
Keywords: RNA-polymerasa I; Cell Nucleolus; Transcription, Genetic; Pol1 Transcription Initiation Complex Proteins; RNA, Ribosomal; HeLa buňky; genetická transkripce; ATPases Associated with Diverse Cellular Activities; Carrier Proteins; lidé; DNA Helicases; ATPázy spojené s různými buněčnými aktivitami; HeLa Cells; DNA-helikasy; Humans; RNA ribozomální; Microscopy, Electron, Transmission; RNA Polymerase I; transportní proteiny; transkripční iniciační komplex Pol1 - proteiny; buněčné jadérko; transmisní elektronová mikroskopie